Unprotected autogenous bone block grafts in the anterior maxilla: resorption rates and clinical outcomes - Kosanić, Ivan; Andrić, Miroslav; Brković, Božidar; Koković, Vladimir; Jurišić, Milan (Vojnosanitetski pregled, 2017)
Background/Aim. The use of autogenous bone grafts for augmentation of the resorbed alveolar ridge is still considered the gold standard in implant dentistry. The aim of this study was to analyze the resorption rate of autogenous bone block grafts from the retromolar region placed in the frontal segment of the upper jaw unprotected by barrier membranes, to assess the stability of implants placed into the grafted bone, as well as to monitor its changes during the healing period. Methods. The study included 18 patients with a total of 20 grafted sites. The residual alveolar ridge was measured before and after the augmentation and prior to implant placement. All implants were restored with provisional crowns within 48 hours after the placement. Implant stability was assessed using resonance frequency analysis. Results. The average period from ridge augmentation to reentry was 5.4 months (range 4–6 months). At reentry the healed alveolar ridge had a mean width of 6.1 ± 1.27 mm. The mean calculated width gain was 3.04 ± 1.22 mm.  The overall surface resorption of block grafts was 0.68 ± 0.69 mm (18.85%).  At the time of implant placement the mean value of implant stability quotient (ISQ) was 71.25 ± 5.77. The lowest ISQ values were noted after three weeks of healing, followed by a gradual increase until week 12. After 12 weeks implants showed significantly higher ISQ values compared to primary stability (p < 0.05 Wilcoxon signed ranks test).  During the 3-years follow-up period no cases of implant loss were recorded. Conclusion. Despite a significant resorption of bone grafts, it was possible to place implants in all the cases and to use the immediate loading protocol without affecting implant survival rate.
Keywords: maxilla; alveolar ridge augmentation; transplantation; autologous; dental implants; bone resorption; treatment outcome